Memantine augmentation in clozapine-refractory schizophrenia: a randomized, double-blind, placebo-controlled crossover study. Issue 9 (6th April 2016) - Veerman, S. R. T.; Schulte, P. F. J.; Smith, J. D.; de Haan, L.
Abstract : Background: Dysfunction of neuroplasticity due to N -methyl-d -aspartate (NMDA) receptor hypofunction may be a causal factor for memory and executive dysfunctioning in schizophrenia. Deregulation of NMDA transmission in the prefrontal cortex may also explain negative and positive symptoms. Clozapine augmentation with memantine targets altered NMDA receptor-mediated neurotransmission in schizophrenia and showed substantial beneficial effects on several symptom domains in a small proof-of-concept study. We evaluate effects of memantine add-on treatment to clozapine for memory and executive function, and negative and positive symptoms in schizophrenia. Method: Clozapine-treated patients with refractory schizophrenia were randomly assigned to 12 weeks of double-blind adjunctive treatment with memantine ( n = 26) or placebo ( n = 26). Crossover occurred after a 2-week placebo wash-out period. Primary endpoints were change from baseline to 12 weeks treatment and 14 weeks to 26 weeks treatment on memory and executive function using the Cambridge Neuropsychological Test Automated Battery (CANTAB), Positive and Negative Syndrome Scale (PANSS), and Clinical Global Impression Severity Scale (CGI-S). Side effects were assessed using the Liverpool University Neuroleptic Side-Effect Rating Scale. Results: When compared with placebo, memantine improved a composite memory score comprising verbal recognition memory and paired associates learning task scores on the CANTAB (effect size = 0.30) and PANSS negative subscale score (effect size = 0.29). Side effects were mild and transient. Conclusions: In patients with clozapine-treated refractory schizophrenia, memantine addition significantly improved verbal and visual memory and negative symptoms without serious adverse effects. These results justify further investigations on long-term memantine augmentation to clozapine in treatment-resistant schizophrenia.